Development of the Design of Mathematical Learning Material Maximum and Minimum Derivative Based on Van Hiele Theory with the Assistance of Geogebra - Chelsia Injilia Runtu; Victor R. Sulangi; Aaltje S. Pangemanan (Journal on Education, 2023)
This study aims to produce mathematics learning tools for maximum and minimum value material based on van Hiele's theory with the help of Geogebra and to determine the quality of learning tools based on validity, practicality and effectiveness. The development model used is the Generic EDR model by Mckenney and Reeves with five stages, namely (1) analysis-exploration, (2) design-construction, (3) evaluation-reflection, (4) preparation of theoretical interpretation-intervention and (5) implementation. The results showed that the average RPP validation score was 4.46, the average LKPD validation score was 4.23, and the THB validation average score was 4.46, with a very good category that met the valid criteria. The teacher and student response questionnaire results, show an average value of 4.33 and 4.29, indicating that the design of learning devices is categorized as very practical. Moreover, the percentage of student learning outcomes test completeness is 90.32. This shows that the design of learning devices is categorized as very effective. Therefore, based on the trial results, the learning device designs developed meet valid, practical and effective criteria